2011
DOI: 10.1364/ol.36.003431
|View full text |Cite
|
Sign up to set email alerts
|

Tunable nonlinear absorption of hydrogenated nanocrystalline silicon

Abstract: Nonlinear absorption (NLA) of hydrogenated nanocrystalline silicon (nc-Si:H) has been investigated through the open aperture Z-scan method for the photon energy of the incident irradiance slightly less than the bandgap of the sample. NLA responses have been observed to be highly sensitive to the wavelength and intensity of the incident irradiance as well as to the bandgap of the sample, indicating greatly tunable NLA of nc-Si:H. The band tail of nc-Si:H appears to play a crucial role in such NLA responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Assuming a two photon absorption (TPA) coefficient of 1 nmW -1 [8] and a reflectivity of the a-Si:H layer of 63%, a deposited energy density of 2 kJcm -3 close to the surface region is derived. To benchmark this value thermal annealing experiments of co-deposited a-Si:H samples on c-Si substrates are conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming a two photon absorption (TPA) coefficient of 1 nmW -1 [8] and a reflectivity of the a-Si:H layer of 63%, a deposited energy density of 2 kJcm -3 close to the surface region is derived. To benchmark this value thermal annealing experiments of co-deposited a-Si:H samples on c-Si substrates are conducted.…”
Section: Resultsmentioning
confidence: 99%
“…For nonlinear absorption, the intensity within the a-Si:H layer can be described by the following differential equation (1) [8]:…”
Section: Resultsmentioning
confidence: 99%
“…Thus, research advances in this field depend critically and primarily on the development of new materials with strong NLO capabilities and effective tailoring of their NLO properties. During the past years, many peculiar NLO materials, such as Au and Pt nanoparticles, [8][9][10] nanocrystalline Si and Si/SiO 2 multilayers, [11][12][13] graphene and graphene-doped polymer, 14,15 PMMA films, 16 and pyrrole methine, 17 have been widely investigated and demonstrated that their application field can be enormously extended by tailoring their NLO properties.…”
mentioning
confidence: 99%
“…18,[21][22][23] The similar SA-to-RSA switching phenomenon has already been found in noble metal nanoparticles 8-10 and nanocrystalline Si films. [11][12][13] Generally, this switching phenomenon is considered to be the consequence of the competition between the ground-state excitation and the nonlinear absorption, which is critically dependent on the laser photon energy, the intensity of the incident radiation, and the band-gap energy of materials. [8][9][10][11][12][13] Nevertheless, our Z-scan experiment was performed at the fixed I 0 and k, which can eliminate the possible inducements of the laser.…”
mentioning
confidence: 99%
See 1 more Smart Citation